The Arabidopsis NIMIN proteins affect NPR1 differentially - Hermann, Meike; Maier, Felix; Masroor, Ashir; Hirth, Sofia; Pfitzner, Artur J.; Pfitzner, Ursula M. (Frontiers in Plant Science, 2013)
NON-EXPRESSOR OF PATHOGENESIS-RELATED GENES1 (NPR1) is the central regulator of the pathogen defense reaction systemic acquired resistance (SAR). NPR1 acts by sensing the SAR signal molecule salicylic acid (SA) to induce expression of PATHOGENESIS-RELATED (PR) genes. Mechanistically, NPR1 is the core of a transcription complex interacting with TGA transcription factors and NIM1 INTERACTING (NIMIN) proteins. Arabidopsis NIMIN1 has been shown to suppress NPR1 activity in transgenic plants. The Arabidopsis NIMIN family comprises four structurally related, yet distinct members. Here, we show that NIMIN1, NIMIN2 and NIMIN3 are expressed differentially, and that the encoded proteins affect expression of the SAR marker PR-1 differentially. NIMIN3 is expressed constitutively at a low level, but NIMIN2 and NIMIN1 are both responsive to SA. While NIMIN2 is an immediate early SA-induced and NPR1-independent gene, NIMIN1 is activated after NIMIN2, but clearly before PR-1. Notably, NIMIN1, like PR-1, depends on NPR1. In a transient assay system, NIMIN3 suppresses SA-induced PR-1 expression, albeit to a lesser extent than NIMIN1, whereas NIMIN2 does not negatively affect PR-1 gene activation. Furthermore, although binding to the same domain in the C-terminus, NIMIN1 and NIMIN2 interact differentially with NPR1, thus providing a molecular basis for their opposing effects on NPR1. Together, our data suggest that the Arabidopsis NIMIN proteins are regulators of the SAR response. We propose that NIMINs act in a strictly consecutive and SA-regulated manner on the SA sensor protein NPR1, enabling NPR1 to monitor progressing threat by pathogens and to promote appropriate defense gene activation at distinct stages of SAR. In this scenario, the defense gene PR-1 is repressed at the onset of SAR by SA-induced, yet instable NIMIN1.